Implementasi Relaksasi Nafas Dalam untuk Menurunkan Tingkat Kecemasan pada Pasien Pra-Anestesi - Wahyuningsih, Ratih; Susanto, Amin; Siwi, Adiratna Sekar (Yayasan Inspirasi El Burhani, 2026)
Introduction: Anxiety is a psychological problem that often arises in patients before undergoing surgery, especially in the pre-anesthesia phase. This condition can affect physiological responses such as increased heart rate, irregular breathing patterns, and high blood pressure. At Ajibarang Regional General Hospital, most pre-anesthesia patients are known to experience moderate to severe anxiety, while standardized non-pharmacological interventions to address this problem are not yet available. Therefore, an effective and easy-to-implement approach is needed to help reduce patient anxiety before surgery. Objective: Assessing the effectiveness of deep breathing relaxation techniques as a non-pharmacological intervention in reducing anxiety levels in pre-anesthesia patients at Ajibarang Regional General Hospital. Method: The intervention was carried out using deep breathing relaxation techniques through controlled breathing exercises designed to stimulate the parasympathetic nervous system, thereby creating a state of relaxation. The patients' anxiety levels were measured using the APAIS (Amsterdam Preoperative Anxiety and Information Scale) instrument before and after the intervention. A total of 30 pre-anesthesia patients underwent this structured therapy process. Result: The results show a significant decrease in anxiety after administering deep breathing relaxation techniques. A total of 30 participants took part in the activity, predominantly adults (96.7%) and women (66.7%). The majority underwent major surgery (83.3%). Before the intervention, anxiety levels were in the moderate (93.3%) and severe (6.7%) categories. After being given deep breathing relaxation techniques, there was a decrease in anxiety, with 93.3% of respondents in the mild anxiety category and no one experiencing severe anxiety. Conclusion: Deep breathing relaxation techniques have been proven effective in reducing anxiety levels in pre-anesthesia patients at Ajibarang Regional General Hospital. This intervention can be recommended as a simple, safe, and easy-to-implement non-pharmacological procedure as part of preoperative preparation in the pre-anesthesia room.